The Effect Of Three-Step Interviews The Students’ Reading Motivation in Teaching Reading - Sri Wahyuni, Widya (Jurnal sosial dan sains, 2024)
Background: This research is motivated by the low reading motivation of students in reading classes during English lessons. This is due to the lack of analysis by some teachers regarding students' needs, which is also caused by the repetitive use of the same learning activities in reading classes, thereby reducing students' interest in learning activities and their desire to read and understand texts. In this study, the researcher focuses on students' intrinsic motivation and uses a learning activity called the Three-Step Interview. Purpose: This study aims to observe the impact of using the Three-Step Interview activity in English teaching, specifically in improving students' reading motivation in reading classes. Methode: This study employs quantitative and qualitative research methods with an experimental approach. The research population consists of 11th-grade science students at SMA Negeri 4 Padang. The sample includes class XI IPA 2 as the experimental group, with 32 students. The Three-Step Interview treatment was given twice, and a comparison treatment was applied twice in the experimental class. The material taught is related to monologue text types based on the curriculum. The instruments provided were questionnaires and tests. Result: The analysis showed an average questionnaire score of 73.97 and 74.43, with an average pre-test score of 79.2 and a post-test score of 81.55. Hypothesis testing was conducted using the t-test, and it was found that the t-table < t-calculated, with values of 1.67 < 1.73 and 1.67 < 1.72. Conclusion: Thus, the hypothesis in this study was accepted, leading the researcher to conclude that the Three-Step Interview significantly improves students' reading motivation in reading classes during English lessons.